U.S. National Security : Policymakers, Processes, and Politics - Sarkesian, Sam C.; Williams, John Allen; Cimbala, Stephen J. (New Delhi Viva Books, 2013)
Completely revised throughout, this fifth edition reflects the new strategic landscape as it has evolved in the aftermath of the September 11 terrorist attacks. It includes issues such as US military involvement in Afghanistan and Iraq, the focus on homeland security, and the impact of the Bush Doctrine.
Include Tables, Figures and Index.
Policymakers, Processes, and Politics.
Keywords: United States -- National security--Decision making -- Military policy--Decision making